A Web-Delivered Multicomponent Intervention for Adolescents with Poorly Controlled Type 1 Diabetes: A Pilot Randomized Controlled Trial. Issue 12 (23rd February 2018) - Stanger, Catherine; Lansing, Amy Hughes; Scherer, Emily; Budney, Alan; Christiano, Ann S; Casella, Samuel J
Abstract: Background: Type 1 diabetes is associated with significant mortality and economic cost. Management of type 1 diabetes involves completing multiple daily adherence behaviors, and many adolescents struggle with self-management and show poor glycemic control. Purpose: The purpose was to conduct an unblinded pilot randomized controlled parallel-group study of a web-delivered multicomponent intervention targeting self-monitoring of blood glucose, working memory, and parent supervision of diabetes care among adolescents with type 1 diabetes. Intervention components included high magnitude incentives for adolescents and parents, motivational and cognitive behavioral therapy and working memory training for adolescents, and training in contingency contracting for parents. Methods: Adolescents ( N = 114) with poorly controlled type 1 diabetes were screened, and N = 61 were randomized using minimum likelihood allocation to usual care (usual care, N = 31) or to a 25-week/15-session web-delivered intervention (WebRx, N = 30). Results: At the end of treatment, adolescents in WebRx had higher self-monitoring of blood glucose ( d = 0.58) (primary outcome), better visual spatial working memory ( d = 0.48) and inhibition ( d = 0.98), and lower HbA1c ( d = 0.45) than those in usual care. WebRx parents reported more frequent review of the adolescent's glucometer ( d = 1.30) and reduced family conflict ( d = 0.56). Between-condition differences were maintained 6 months later in self-monitoring of blood glucose ( d = 0.42), visual spatial working memory ( d = 0.76), family conflict ( d = 0.50), and HbA1c ( d = 0.44). Conclusions: Results showing sustained effects on self-monitoring of blood glucose and HbA1c support moving forward with a larger trial to test this innovative web-delivered and multicomponent intervention. ClinicalTrials.gov Number (NCT01722643) Abstract : Teens with type 1 diabetes showed sustained improved glycemic control compared to usual care following a web-delivered intervention that included incentives for blood glucose checks, working memory training, and counseling for teens and parents.